Marketing of Fruits and Vegetables in the Agricultural Produce Marketing Committee, Vashi, Navi Mumbai - Samirkumar R. Bhadani; Snehal Mishra (Archives of Current Research International, 2024)
The research focuses on understanding the marketing dynamics and identifying areas for improvement in the supply chain. This study examines the sales and purchase practices, marketing costs, and factors influencing prices in the Agricultural Produce Market Committee (APMC) Vashi market for fruits and vegetables. Data were collected from the 30 farmers, 40 wholesalers/commission agents and 30 retailers through structured questionnaires, between January 2024 and April 2024 and a purposive sampling technique was chosen to gather specific information. The findings reveal that middlemen, such as Local Agent (35%), pre-harvest contractors (15%) and commission agents (12.5%), play a significant role in the supply chain, leading to increased costs and reduced profits for farmers. The study also highlights notable variations in marketing costs, margins, and price spreads across different commodities. Market competition emerges as a crucial factor influencing prices, emphasizing the need for a competitive market environment.